Accumulation of 137Cs by lichen Hypogymnia physodes (on the example of the Gomel region) - Seglin, Veronika N.; Hramchenkova, Оlga М.; Dvornik, Aliaksandr A. (Journal of the Belarusian State University. Ecology, 2021)
The paper presents the results of determining the 137Cs content in the biomass of the lichen Hypogymnia physodes, which growing in pine forests on the territory of the Gomel region with various levels of radioactive contamination.The research was carried out both in conditionally clean and radioactively contaminated areas with 137Cs soil contamination density from 37 to 1488 kBq m-2. The high accumulating capacity of the lichen Hypogymnia physodes in relation to 137Cs was shown, as well as an increase in the concentration of the radionuclide in the lichens biomass with an increase in the density of soil contamination. Differences in 137Cs accumulation by the lichen Hypogymnia physodes, growing in uneven-aged pine stands, were noted. The lowest concentrations of 137Cs were noted in the samples growing in mature pine forests, while thalli sampled from young pine stands contain significant amounts of the radionuclide.
Keywords: epiphytic lichen; radionuclides; biomonitor; bioaccumulation; pine stands